TLR3 polymorphisms are associated with the severity of hand, foot, and mouth disease caused by enterovirus A71 in a Chinese children population. Issue 11 (10th June 2021) - Chen, Guo‐Ping; Xiang, Kun; Sun, Liang; Shi, Yong‐Lin; Meng, Can; Song, Lv; Liu, Rui‐Shan; Li, Wei‐Dong; Pan, Hai‐Feng
Abstract: Hand, foot,  and mouth disease (HFMD) caused by enterovirus A71 (EV‐A71) is a contagious viral disease, and toll‐like receptors (TLRs) play essential roles in resisting the pathogen. The aim of this study was to assess the potential relationship between several TLRs polymorphisms and the HFMD severity in a Chinese children population. A total of 328 Chinese children with HFMD were included in the present study. The polymorphisms of TLR3 (rs3775290, rs3775291, rs3775296, rs1879026, rs5743312, rs5743313, rs5743303, rs13126816, and rs3775292), TLR4 (rs4986790, rs4986791, rs2149356, rs11536889, and rs41426344), TLR7 (rs179009, rs179010, rs179016, rs3853839, rs2302267, rs1634323, and rs5741880), and TLR8 (rs3764880, rs2159377, rs2407992, rs5744080, rs3747414, rs3764879, and rs5744069) genes were selected. The study indicated that individuals with the GG genotype of TLR3 single‐nucleotide polymorphism rs1879026 had a higher risk of developing severe cases (GG vs. GT: OR = 1.875; 95% CI, 1.183–2.971; p  = .007). Meanwhile, TLR3 rs3775290 CC genotype and C allele were associated with lower disease severity in females (CC vs. CT: OR = 0.350; 95% CI, 0.163–0.751; p  = .006; C vs. T: OR = 0.566; 95% CI, 0.332–0.965; p  = .036). TLR3 rs3775291 CC genotype showed 2.537 folds higher risk of developing severe cases in females (CC vs. CT: OR = 2.537; 95% CI, 1.108–5.806; p  = .026). Moreover, TLR3 rs1879026 GG genotype was found to be related to increased risk of severe cases in males (GG vs. GT: OR = 2.076; 95% CI, 1.144–3.768; p  = .016). The current findings show that the genetic variants of TLR3 rs1879026, rs3775290, and rs3775291 are associated with the severity of EV‐A71‐associated HFMD in a Chinese children population.